Analysis of flood insurance premium amount using Fuzzy Inference of Sugeno Method - Kankan Parmikanti, Sukono,; Panggabean, Nerly; Agung Prabowo, Herlina Napitupulu, (Opción, 2020)
The study aims to investigate the analysis of flood insurance premium amount using the Fuzzy Inference of Sugeno Method by considering the criteria of community income, community expenditure, and flood zone. As a result, the premiums paid by each household are IDR 9,688.65 per month for residents of Bojongsoang District, and IDR 10,256.27 per month for residents of Baleendah District. In conclusion, three criteria are affecting the decision determination of premium value, namely the average income of the community, their expenditure monthly, and the flood zone area of community Bojongsoang and Baleendah District in Citarum River.